1995
DOI: 10.4050/jahs.40.44
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Dynamics of Helicopter Slung Load Systems

Abstract: Equations of motion are derived for general slung load systems. Systematic approaches have not previously been studied for deriving slung load dynamic models, hut an interest in simulation, analysis, and control for slung loads carried by two o r more helicopters motivates attention to this topic. Slung load systems a r e approximated as several rigid bodies connected by suspensions consisting of straight line cables and links which can be assumed elastic o r inelastic and which transmit force only along the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…However, several studies have addressed the behavior of configurations with multiple attachment points. Reference will only be made here to an assessment of the state of the art for multi-point suspension configurations, presented by Sheldon [10], to an in-depth theoretical study of the dynamics of a 2-suspension point, 4-cable load configuration subsequently carried out by Prabhakar [11], and to a paper by Cicolani et al [12] which proposes a formulation valid for arbitrary numbers of aircraft, loads, and suspension points.…”
Section: More Recently Cicolani Et Al Have Reported the Results Of mentioning
confidence: 99%
“…However, several studies have addressed the behavior of configurations with multiple attachment points. Reference will only be made here to an assessment of the state of the art for multi-point suspension configurations, presented by Sheldon [10], to an in-depth theoretical study of the dynamics of a 2-suspension point, 4-cable load configuration subsequently carried out by Prabhakar [11], and to a paper by Cicolani et al [12] which proposes a formulation valid for arbitrary numbers of aircraft, loads, and suspension points.…”
Section: More Recently Cicolani Et Al Have Reported the Results Of mentioning
confidence: 99%
“…Searching in the specialist literature for papers on this particular area of load failures revealed that the subject has not been well investigated. The publications found are somewhat sparse, many of them relating only to the subject of modelling of the dynamics of a helicopter with a slung load (1)(2)(3)(4)(5)(6)(7) , the dynamic instabilities of a slung load (8)(9)(10)(11)(12)(13)(14)(15)(16)(17) , handling qualities of helicopter/slung load system (18)(19)(20)(21) or modelling the control system of a helicopter with a slung load (22,23) . A few publications have been identified dealing with load problems; however, they address mainly a rather different problem from that considered in the present paper, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION There are various applications for aerial load transportation such as usage in construction, military operations, emergency response, or delivering packages. Load transportation with the cable-suspended load has been studied traditionally for a helicopter [1], [2] or for small unmanned aerial vehicles such as quadrotor UAVs [3], [4], [5].…”
mentioning
confidence: 99%